Impact of different climates on the resistance of concrete to natural carbonation. (20th August 2019) - Huy Vu, Quoc; Pham, Gabriel; Chonier, Alain; Brouard, Eric; Rathnarajan, Sundar; Pillai, Radhakrishna; Gettu, Ravindra; Santhanam, Manu; Aguayo, Federico; Folliard, Kevin J.; Thomas, Michael D.; Moffat, Ted; et al.
Highlights: Sheltered natural carbonation can be similar between different climates. Huge impact of curing on natural carbonation for very early age (i.e. 1 day) Impact of curing is negligible for advanced curing age, regardless of cement type. Strong impact of precipitation on natural carbonation. The higher the number of rainy days, the lower the carbonation speed. Abstract: This paper describes a unique international inter-laboratory study on the carbonation resistance of concrete prepared with different supplementary cementing materials. Concrete specimens – from 45 different concrete mixtures – prepared centrally in Lafarge Centre de Recherche (France) were shipped in a sealed condition to 4 other academia research laboratories (located in USA, Canada, India and China). The specimens were exposed to the ambient environments and atmospheric CO2 concentrations in the five locations, including Lafarge Centre de Recherche in France, in both sheltered and unsheltered condition for a period of 5 years. Measurements of carbonation depth were performed at periodic intervals, and the data was analyzed to assess the influence of climatic conditions on the resistance to carbonation. The results indicate that the general trend of carbonation is not much different irrespective of the macroclimate. Further, the number of rainy days seems to have a more significant influence on the progress of carbonation than the total rainfall in the region.